Retailing : shopping, society, space - O'Brien, Larry, 1957- (Routledge library editions. Retailing and distribution, 2013)
This textbook provides an up-to-date, comprehensive and fully integrated treatment of retailing as a) and industry, b) a force shaping social attitudes and contemporary culture, and c) a force for change in modern townscapes. Unlike other texts which focus on specific topics, this book provides a treatment of retailing which will appeal to geographers, economists, planners and social scientists. First published 1991.